Metabolite characterization of fifteen by-products of the coffee production chain: From farm to factory - Rodrigues da Silva, Mariana [UNESP]; Sanchez Bragagnolo, Felipe [UNESP]; Lajarim Carneiro, Renato; de Oliveira Carvalho Pereira, Isabela [UNESP]; Aquino Ribeiro, José Antonio; Martins Rodrigues, Clenilson; Jelley, Rebecca E.; Fedrizzi, Bruno; Soleo Funari, Cristiano [UNESP] (Elsevier, 2022)
Approximately 11.4 million tonnes of solid by-products and an increased amount of waste water will be generated during the 2020/21 coffee harvest. There are currently no truly value-adding uses for these potentially environmentally threatening species. This work presents the most wide-ranging chemical investigation of coffee by-products collected from farms to factories, including eight never previously investigated. Twenty compounds were found for the first time in coffee by-products including the bioactive neomangiferin, kaempferol-3-O-rutinoside, lup-20(29)-en-3-one and 3,4-dimethoxy cinnamic acid. Five by-products generated inside a factory showed caffeine (53.0–17.0 mg.g−1) and/or chlorogenic acid (72.9–10.1 mg.g−1) content comparable to coffee beans, while mature leaf from plant pruning presented not only high contents of both compounds (16.4 and 38.9 mg.g-1, respectively), but also of mangiferin (19.4 mg.g-1) besides a variety of flavonoids. Such by-products are a source of a range of bioactive compounds and could be explored with potential economic and certainly environmental benefits.
Keywords: (-)-Epicatechin (PubChem CID 72276); 3,4-dimethoxy cinnamic acid (PubChem CID 717531); 3-O-caffeoylquinic acid (PubChem CID 1794427); 4-O-caffeoylquinic acid (PubChem CID 9798666); 5-O-caffeoylquinic acid (PubChem CID 5280633); Agri-food by-products; Biorefinery; Caffeine (PubChem CID 2519); GC-MS; Kaempferol-3-O-rutinoside (PubChem CID 5318767); Lup-20(29)-en-3-one (PubChem CID 323075); Mangiferin (PubChem CID 5281647); Neomangiferin (PubChem CID 6918448); Two-liquid phase extraction; UHPLC-PAD/UV-ESI-QTOF-MS/MS; Waste valorization